Sapiens : a graphic history, the birth of humankind - Harari, Yuval Noah (London Penguin Random House, 2020)
In this first volume of the adaptation of his ground-breaking book, renowned historian Yuval Harari tells the story of humankind's creation and evolution, exploring the ways in which biology and history have defined us and enhanced our understanding of what it means to be "human". From examining the role evolving humans have played in the global ecosystem to charting the rise of empires, Sapiens challenges us to reconsider accepted beliefs, connect past developments with contemporary concerns, and view specific events within the context of larger ideas.
Keywords: Technology and civilization; World history; Civilization